Antioxidant Activity Of Nanoemulsion Of Beet Fruit Extract Using The Dpph Method - Nisa, Farhatun (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Free radicals are one of many forms of reactive oxygen sorts known for having unpaired electrons. The presence of free radicals in the body can cause damage such as premature aging, characterized by the appearance of wrinkles. This damage can be countered with antioxidant compounds. Beetroot is one of the fruits with antioxidant properties due to the presence of betacyanin compounds from the flavonoid group. This research aims to identify the antioxidant activity and IC50 value of beetroot (Beta vulgaris L.) extract nanoemulsion formulations using the DPPH method. Nanoemulsion formulations were prepared with varying concentrations of beetroot extract at 1% (X1), 3% (X2), and 5% (X3) to determine which concentration has the best antioxidant activity. Quality evaluation of the nanoemulsion formulations was also conducted, including organoleptic tests, pH tests, and homogeneity tests. The results showed that the beetroot extract nanoemulsion formulations have antioxidant activity and meet the requirements for physical properties and formulation stability. Nanoemulsion formulations with 5% (X3) beetroot extract content exhibited the best antioxidant activity with an IC50 value of 136.475 ppm.